Physical activity for older adults: Physical Activity Guidelines for the Brazilian Population - Coelho-Ravagnani, Christianne de Faria (2021)
At the Ministry of Health initiative, in collaboration with national researchers, the first Physical Activity (PA) Guidelines for the Brazilian Population was prepared, including recommendations for the various stages of life and special populations. This study aims to present the methodological process of the chapter on PA recommendations for the older adults. The Older Adults Work Group had 11 researchers/professionals who held weekly virtual meetings, made a systematic review of reviews, which included 50 articles, and promoted a listening among older adults (n = 22), managers (n = 17) and professionals (n = 143) from all country regions, through telephone interviews and online forms. Based on the review and the listening results, a first version of the PA Guidelines for the older adults was elaborated, which was submitted to public consultation. Forty-six valid suggestions were received for the Guide’s writing, of which 34 were accepted and incorporated into the final text since they had technical and/or social relevance. As results, the Guidelines highlight the major benefits of PA for the older adults, such as enhancement of the physical, mental and social aspects, and recommends a minimum of 150 minutes of moderate PA or 75 minutes of vigorous PA per week, considering PA in free time, getting to and from places and household chores, as well as in work/study time. It is believed that these Guidelines will help the older adults and health professionals to get to know the benefits of PA, the recommended amount, and the different possibilities of practice through culturally appropriate messages and examples. Politically, it will reinforce the central role of PA in the prevention and control of chronic non-communicable diseases, boosting actions for its dissemination and implantation.